Elaborazione di Piattaforma GIS sul fattore di Rischio alluvionale nel comprensorio del Comune di Sora (Fr) - Cuzzocrea, Fabio; Lucidi, Stefano (GEOmedia, 2019)
The support of digital cartography is now very widespread in the management of information and the National Fire Brigade, now for several years, studies the possible applications of this technology to emergency technical rescue activities. These IT tools are very useful in management assessments during the alert, alarm and emergency phase, favouring the prediction and assessment of remote damage scenarios. The systems allow the reading of data directly from digital cartography, from which "hidden" information can be deduced, in addition to those already reported in symbols in the initial screens. Moreover, the systems allow an easy comparison between the information on different maps, which can be read directly together on the same map. The article illustrates the experience of the Frosinone VVF Command in the development of a cartographic platform, in which the different damage scenarios resulting from a hypothetical flood in the Municipality of Sora were simulated.